Analysis of the wettability of solutions for endodontic irrigation - T. N. Manak; O. S. Savostsikоva; A. V. Mitronin (Эндодонтия Today)
A comparative analysis of the contact angle wetting of imported and new domestic products for endodontic irrigation has been carried out. The obtained data show that the range of products for endodontic irrigation developed by the Department of General Dentistry of the Belarussian State Medical University and BelAseptika-Des JLK, which includes the original 3% sodium hypochlorite solution for antiseptic treatment and chemical dilatation of the root canals of teeth «Dentiseptin» and «Endoseptin 17» for revealing the mouth of the root canals and their expansion, which contains solutions of EDTA sodium salts, is not inferior in its «wettability» properties, but also exceeds that of foreign analogues. Since penetration of the irrigant is directly related to wettability, this property can serve as a good criterion for assessing the effectiveness of irrigation.